The UGT1A6_19_GG genotype is a breast cancer risk factor - Justenhoven, Christina; Obazee, Ofure; Winter, Stefan; Rabstein, Sylvia; Lotz, Anne; Harth, Volker; Pesch, Beate; Bruening, Thomas; Baisch, Christian; Hartikainen, Jaana M.; Mannermaa, Arto; Winqvist, Robert; et al. (Frontiers in Genetics, 2013)
Validation of an association between the UGT1A6_19_T>G (rs6759892) polymorphism and overall breast cancer risk. A pilot study included two population-based case-control studies from Germany (MARIE-GENICA). An independent validation study comprised four independent breast cancer case-control studies from Finland (KBCP, OBCS), Germany (BBCC) and Sweden (SASBAC). The pooled analysis included 7,418 cases and 8,720 controls from all six studies. Participants were of European descent. Genotyping was done by MALDI-TOF MS and statistical analysis was performed by logistic regression adjusted for age and study. The increased overall breast cancer risk for women with the UGT1A6_19_GG genotype which was observed in the pilot study was confirmed in the set of four independent study collections (OR 1.13, 95% CI 1.05-1.22; p = 0.001). The pooled study showed a similar effect (OR 1.09, 95% CI 1.04-1.14; p = 0.001). We confirmed the association of UGT1A6_19_GG with increased overall breast cancer risk and conclude that our result from a well powered multi-stage study adds a novel candidate to the panel of validated breast cancer susceptibility loci.